Ethical Awareness in the Use of Information and Communication Technology in the Context of Computer Criminal Behavior Among Souphanouvong University Students - Bounkeomany, Paphaychit; KINGSADA, Youtthasack; HER, Lee; PHONGSAWATH, Salunyoo; PHANTOUAMATH, Poutthalack (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study objectives are to: 1) Study the ethical awareness of ICT usage in computer system criminal behavior; 2) Examine the behavior ICT usage that constitutes computer system crimes; 3) Compare differences in individual factors related to ICT behavior among students. The study involves 3 student groups: IT Business students, IT Engineering students and Computer Engineering students. The sample groups are 117 students which 24 are women. The instrument used in the study was a closed-ended questionnaire with both multiple-choice and 5-point ratio. The statistics used in the analysis included: percentage (%), mean () and One-Way ANOVA test. The results of the study found that: 1) The level of ethical awareness in the use of information and communication technology has a total average percentage of 87.17%, which is the highest level of awareness compared to the level value, 2) Behavior in the use of information and communication technology as a computer crime has a total average (= 1.33), which is the lowest level of computer crime behavior, 3) The results of the comparison analysis showed that different groups of students will have different behaviors in the use of information and communication technology as a computer crime. When considered in pairs with the results of the analysis, it was found that there was no difference between students in the IT Business major and students in the Computer Engineering major; The pairs of students majoring in Computer Engineering and students majoring in IT Engineering, and the pairs of students majoring in IT Engineering and students majoring in IT Business, will have different behaviors in using information and communication technology as computer crimes with a significance level of 0.05.